دور الأجهزة العليا للرقابة المالية والمحاسبة في مراجعة المسؤولية الاجتماعية والبيئية للشركات: دراسة مسحيّة للأدب المحاسبي (Comprehensive Journal of Science, 2026)
This paper examines the role of supreme audit institutions in reviewing corporate social and environmental responsibility through a survey of relevant accounting literature. The study aims to highlight how these institutions monitor companies' adherence to environmental and social standards and the effectiveness of this oversight in promoting transparency and accountability        The literature indicates a variation in the effectiveness of supreme audit institutions based on the legal and economic context of each country. In developed countries, institutions have broad authorities and adhere to international standards, whereas in developing countries, oversight may be limited due to resource and legislative constraints                                                                                          The study recommends improving legislation, enhancing human capacities, and expanding the use of technology and international collaboration to better the effectiveness of oversight on social and environmental responsibility
Keywords: Supreme Audit Institutions - Social and Environmental Responsibility